Muscle activity, leg stiffness, and kinematics during unresisted and resisted sprinting conditions - Zabaloy, S.; Carlos-Vivas, J.; Freitas, T. T.; Pareja-Blanco, F.; Loturco, I.; Comyns, T.; Gálvez-González, J.; Alcaraz, P. E. (The Journal of Strength and Conditioning Research, 2022)
This study aimed to compare muscle activity, leg stiffness, and kinematics (contact and flight time [FT], stride length and frequency, and trunk angle [TA]) of unloaded sprinting to resisted sprint (RST) using different loads. Twelve male rugby players (age: 23.5 ± 5.1 years; height: 1.79 ± 0.04 m; body mass 82.5 ± 13.1 kg) performed 30-m sprints using different loading conditions (0, 10, 30 and 50% of velocity loss—Vloss—from the maximum velocity reached under unloaded condition). Muscle activity from 4 muscles (biceps femoris long head, rectus femoris [RF], gluteus medius and gastrocnemius), leg stiffness (Kleg), and kinematics were measured during the acceleration and maximum velocity (Vmax) phases of each sprint. Heavier loads led to significantly lower biceps femoris long head activation and higher rectus femoris activity (p < 0.01-0.05). Significant reductions in Kleg were observed as loading increased (p < 0.001-0.05). Kinematic variables showed substantial changes with higher loads during the acceleration and Vmax phase. In conclusion, the heavier the sled load, the higher the disruptions in muscle activity, Kleg, and kinematics. When coaches and practitioners intend to conduct resisted sprint training sessions without provoking great disruptions in sprint technique, very-heavy sled loads (greater than 30% Vloss) should be avoided. However, heavy sled loads may allow athletes to keep specific positions of the early acceleration phase for longer time intervals (i.e., first 2-3 strides during unresisted sprints).